Simon V of Montfort: The exercise and aims of independent Baronial power at home and on crusade, 1195-1218 - Lippiatt, G (2015)
Historians of political development in the High Middle Ages often focus on the late twelfth and early thirteenth centuries as the generations in which monarchy finally triumphed over aristocracy to create a monopoly on governing institutions in western Europe. However, it was precisely in this period that Simon of Montfort emerged from his modest forest lordship in France to conquer a principality stretching from the Pyrenees to the Rhône. A remarkable ascendancy in any period, it is perhaps especially so in its contrast with the accepted historiographical narrative. Nonetheless, Simon has been largely overlooked on his own terms, especially by English historiography. Despite the numerous works over the course of the twentieth and twenty-first centuries devoted to the Albigensian Crusade, only a handful of biographies of Simon have been published, none of which are in English. Furthermore, those French works dedicated to his life have been little more than narrative retellings of the Albigensian Crusade from Simon's perspective, with an introductory chapter or two about his family background, participation in the Fourth Crusade, and life in France. French domination of the historiography has also prevented any deep exploration of Simon’s English connexions, chiefly his inheritance of the earldom of Leicester in 1206. The substantial inquest regulating this inheritance awaits publication by David Crouch, but at least forty other acts from Simon's life remain unedited, despite increased interest in the Albigensian Crusade and several having been catalogued for over a century. Though one of the aims of this thesis is to correct the lack of Anglophone attention paid to this seminal figure of the early thirteenth century, a biographical study of Simon has consequences beyond the man himself. The inheritance of his claims to the Midi by the French Crown after his death means that his documents survive in a volume uncharacteristic of a baron of his station. The dedicated narrative history of his career provided by Peter of Vaux-de-Cernay's Hystoria albigensis is likewise the most intimate prose portrait of a comital figure available from the period. Thus Simon’s life is perhaps the best recorded of his contemporary peers, offering a rare insight into the priorities and means of a baron’s administration of his lands and leadership of a crusade. Moreover, despite the supposed triumph of monarchy during his lifetime, Simon’s meteoric career took place largely outside of royal auspices and sought crowned approval for its gains only after the fact. Simon’s experience was certainly exceptional, both in itself and in the volume of its narrative and documentary records, but it nevertheless provides a challenge to an uncomplicated or teleological understanding of contemporary politics as effectively national affairs directed by kings. Rather than spend his life in the train of one particular king, as did his contemporaries William the Marshal or William of Barres, Simon's career, in its various geographical manifestations, saw him in the lordship of three different Crowns: France, England, and Aragon. Though his relations with the first of these were almost entirely amicable—if not always harmonious—he was more often in open conflict with the latter two. As a crusader, Simon was also subject to a fourth lord, the pope, for the major events of his career. But even while executing papal mandates, Simon at times came into conflict with the distant will of Rome. However, none of these lords successfully prevented Simon's ascendancy. Angevin and Barcan influence in the Midi was drastically handicapped by the Albigensian Crusade, in the latter case, definitively. And while popes may have disagreed with some particulars of Simon's prosecution of the crusade, he remained their best hope for curbing the threat of heresy. One reason for Simon's success in the face of opposition was his ability to exploit the margins of monarchical authority, retreating from his obligations of fidelity to lord in favour of another, thus presenting himself as a legitimate actor while interfering with the designs of a nominal superior. Such independence, however, required alternative bases for his own power that could not be found in the largely rhetorical refuge offered by a distant overlord. In the absence of support from above, Simon worked to cultivate relationships with his social peers and the lesser French nobility. Notably, however, outside of his immediate family, adherence to his cause more often came from his socially inferior neighbours and those with common spiritual devotions than from his wider kinship network. His extended family, of roughly equivalent social standing to himself, were more interested in following the French king in his campaigns to consolidate royal power than investing deeply in Simon’s crusade. However, those with similar ideological concerns or dependent on his success saw in Simon a charismatic and effective leader worthy of their allegiance. For Simon himself, the crusade was animated by the programme of reform advocated by the Cistercians and certain Parisian theologians. His context was permeated by the reformers, especially in his close connexions with the abbey of Vaux-de-Cernay. Concerns about just war, the liberation of the Holy Land, ecclesiastical liberty, sexual morality, and the purgation of heresy espoused by Cistercians and schoolmen were reflected in Simon’s career. He was more than a simple cipher for ecclesiastical priorities: his campaigns and government were ambiguous in their attitude toward mercenaries and complicit in the problem of usury. Nevertheless, Simon’s crusades to both Syria and the Midi demonstrated a remarkable dedication to building a Christian republic according to the vision of the reformers. But Simon was not always a crusader, and the majority of his career—though not the majority of its records—took place in his ancestral lands in France. Though his time in the shadow of Paris does not offer the same salient examples of baronial independence as his conquest of the Midi, it does provide a crucial glimpse at the ordinary exercise of aristocratic government on a more intimate scale. His forest lordship furnished lessons of administration that would prove relevant to his rule in the Midi, such as the diplomatic projection of authority, the value of seigneurial continuity, the economic benefit of thriving towns, the necessity of an intensively participating chivalric following, and the advantage of wide ecclesiastical patronage. Similarly, Simon’s brief seisin and subsequent disseisin of the honor of Leicester demonstrated the fragility of his power when many of these elements were lacking. In addition to abstract lessons of governance, his northern lands also provided the financial backing necessary for at least the initial phases of his crusading career. Thus Simon's lordship in France and England, though not nearly as autonomous as in the Midi, is far from irrelevant to his later manifestations of independence: it rather informs his later government and even made it possible. That is not to say that Simon’s administration of the Midi was simply that of his French fief writ large. Most significantly, his possessions in the south were obtained by conquest rather than inheritance. Moreover, that conquest was ideologically justified by a characterisation of the previous lords as deficient protectors of the Christian republic. As a result, the image and patronage cultivated by Simon in the viscounties of Béziers and Carcassonne made little effort to reflect Trencavel traditions. This negative difference was supplemented by the positive distinction enshrined in the Statutes of Pamiers, which decisively implemented the reform programme embraced by Simon and neglected by his predecessors. But the Trencavels had been culturally of a piece with their subjects, and the influence of heresy and resistance to neogregorian ideas among the indigenous aristocracy fomented serious resistance to Simon in the first years of the crusade. Simon countered this not only through superior generalship, but by coopting what native lords and burghers he could, conserving the loyalty of his French followers with confiscated fiefs, generally respecting urban autonomy, and lavishing patronage on local bishops and Cistercian houses. Due to the crusading context of his conquests, his implementation of government was dynamic rather than dogmatic, balancing the demands of reform with the practical constraints of a largely hostile populace. This dynamism, paradoxically, broke down just as the crusade reached its zenith in the acquisition of the county of Toulouse. Though Simon’s introduction of French feudal patterns and antiheretical policies still stood in stark contrast to the often ineffectual and tolerant attitude of the Saint-Gilles, the dispossessed family's dynastic eminence offered more incentive to maintain continuity with Egidian iconography and at least cultivate personal ties with traditionally favoured Benedictine abbeys. As in the viscounties, cultivation of local nobles, appointment of French followers to key posts, preservation of urban liberties, and patronage of Cistercians and bishops all undergirded Simon’s regime. But even with this broad base of support, Simon was finally undone by the southern resurgence that focussed on the fatal exception to his characteristic urban lenience: Toulouse. His inability to accommodate the consular independence of his ostensible capital allowed it to serve as a rallying point for the disaffected and dispossessed aristocracy of the region, and it was before the red walls of Tolosa dolosa that Simon met his bloody end. Despite his death and the subsequent collapse of his principality, Simon's years in power clearly demonstrate a commitment to government—represented most clearly by the Statutes of Pamiers—usually associated by historians with royal regimes. The achievements and—more importantly—the aspirations of Simon’s career suggest that this may be too narrow. Not only were kings still unable to control their barons at the turn of the thirteenth century, they were not the only lords interested in the creation of effective government. Indeed, Simon's preoccupation with government paradoxically contributed to the collapse of his regime: had he been less interested in implementing his reforms and binding his subjects to intensive participation in his regime, he might not have engendered the resentment that cost him his life. A study of Simon of Montfort, therefore, suggests a corrective to a focus on monarchies as the exclusive engines of medieval government: exceptional though Simon may have been, his career provides a valuable glimpse of both the means and concerns of baronial autonomy at the turn of the thirteenth century.